The Development of Model on Field Experience Teaching Practice Program (PPL) Based on Lesson Plan in Islamic Education Study Program(PAI) in Islamic State Institute Pontianak - Razi, Fahrul; Ma'ruf, Ma'ruf (The Pontianak State Institute of Islamic Studies, 2021)
This study is aimed to develop a model of lesson study for the Teaching Practice Program (PPL) to improve students’ ability in implementing instruction for prospective teachers of Islamic Education Study Program(PAI) at the Islamic State Institute (IAIN) Pontianak.The R D and experimental methods were used and carried out at the PAI in Education and Teacher Training Faculty(FTIK) of the IAIN Pontianak. Data were collected using the inventory, observation sheets, FGD and documentation. Validation of the contents was analyzed by expert judgment, while descriptive and comparative data analysis was conducted using t-test for independent samples. All was done with IBM SPSS 20.This research revealed that the model of lesson study implemented at PPL activities improved teaching ability of prospective teachers of PAI at IAIN Pontianak. In particular, it was found that: (1) characteristics of supervisors, teacher tutors and students significantly determined the success of the model of Lesson Study in the implementation of PPL; (2) the process of implementation of the Lesson Study-based PPL model was developed through steps of plan, do and see; (3) the Lesson Study-based PPL model had an influence on the ability of prospective teachers of PAI IAIN Pontianak to implement instruction. The results of this research recommended that PPL should be conducted with a Lesson Study approach.